Investigation and Performance Evaluation of Novel Single-Switch High-Gain DC-DC Converters for DC Microgrid Applications - M. Diwakar Naik; U. Vinatha; M. Venkatesh Naik; Praveen Kumar Bonthagorla (IEEE Access)
This paper introduces a novel single-switch, non-isolated high-gain DC-DC converter for solar photovoltaic (PV) and fuel-cell (FC) applications. These energy sources typically provide a continuous supply of current, necessitating a high-gain DC-DC converter that operates in continuous conduction mode (CCM). This converter draws a continuous input current from the supply and delivers a continuous output current to the load. The performance of the converter is thoroughly analyzed through the development of a state-space model and the derivation of the small signal transfer function, which helps in understanding the converter’s dynamic behavior. Detailed comparisons with existing converters are also presented. Furthermore, an output voltage controller is designed using the k-factor method to effectively regulate the output voltage without requiring a current sensor, even in the presence of input voltage variations. To validate the effectiveness of the converter and its controller, a 150 W prototype was constructed and experimentally verified in a laboratory setting.